Optimalisasi Pemanfaatan Limbah Ternak melalui Pembuatan Pupuk Organik Bokashi untuk Meningkatkan Kemandirian Kelompok Tani - Mufida, Inayatul; Muhtiawati, Syahrila; Firmansyah, Dwiky Aries; Berliana, Amanda Putri; Auni, Nadia Luthfi; Amin, Angga Sahrul; Qoyyimah, Ulil; Meilani, Nera Anyamita; Hersa M, Muhammad Rafli; Muhtiawati, Syahrifa; Ummi, Zahrotul; Prayogi, Dimas Artha; Priadi, Eeng (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Farmer groups in Kebonan Village face the problem of untreated goat manure, which often causes environmental pollution. This community service aimed to empower farmers by processing livestock waste into bokashi organic fertilizer with economic value. The method applied was Participatory Action Research (PAR), involving farmers in all stages of the program, including problem identification, socialization, and hands-on practice of bokashi production. The process consisted of material preparation, 7-14 days of fermentation, and product packaging. The results showed improved farmer’s knowledge and skills in waste management, and the produced bokashi met quality standards with neutral pH, stable temperature, dark brownish color, fine texture, and odorless condition. This program successfully reduced livestock waste, improved soil fertility, and supported sustainable agriculture based on local resources.